The Phaeodactylum genome reveals the evolutionary history of diatom genomes - Bowler, Chris; Allen, Andrew E.; Badger, Jonathan H.; Grimwood, Jane; Jabbari, Kamel; Kuo, Alan; Maheswari, Uma; Martens, Cindy; Maumus, Florian; Otillar, Robert P.; Rayko, Edda; Salamov, Asaf; et al. (My University, 2008)
Diatoms are photosynthetic secondary endosymbionts found throughout marine and freshwater environments, and are believed to be responsible for around one-fifth of the primary productivity on Earth. The genome sequence of the marine centric diatom Thalassiosira pseudonana was recently reported, revealing a wealth of information about diatom biology. Here we report the complete genome sequence of the pennate diatom Phaeodactylum tricornutum and compare it with that of T. pseudonana to clarify evolutionary origins, functional significance and ubiquity of these features throughout diatoms. In spite of the fact that the pennate and centric lineages have only been diverging for 90 million years, their genome structures are dramatically different and a substantial fraction of genes (40%) are not shared by these representatives of the two lineages. Analysis of molecular divergence compared with yeasts and metazoans reveals rapid rates of gene diversification in diatoms. Contributing factors include selective gene family expansions, differential losses and gains of genes and introns, and differential mobilization of transposable elements. Most significantly, we document the presence of hundreds of genes from bacteria. More than 300 of these gene transfers are found in both diatoms, attesting to their ancient origins, and many are likely to provide novel possibilities for metabolite management and for perception of environmental signals. These findings go a long way towards explaining the incredible diversity and success of the diatoms in contemporary oceans.
Keywords: 570